Serum neutralization with different types and subtypes of bovine herpesvirus 1 and 5 - Holz,Carine Lidiane (2010)
The serum neutralization (SN) test is the gold standard method to measure neutralizing antibodies to bovine herpesviruses. However, in view of the further subdivisions of bovine herpesviruses in types/subtypes, defining which virus to use at challenge in SN tests may be difficult. In view of that, this study was carried out to re-evaluate (SN) sensitivity with different types/subtypes of bovine herpesviruses types 1 (BoHV-1) and 5 (BoHV-5) as challenge viruses. Bovine sera (n=810) were collected from two distinct geographic regions and tested by SN with three type 1 viruses (BoHV-1.1 strains "Los Angeles" and "EVI123/98"; BoHV-1.2a strain "SV265/96") and three type 5 viruses (BoHV-5a strain "EVI88/95"; BoHV-5b strain "A663" and BoHV-5c "ISO97/95"). SN tests were performed with a 1 hour incubation of the serum-virus mixtures at 37ºC against 100 TCID50 of each of the viruses. SN sensitivity varied greatly depending on the challenge virus used in the test. The highest sensitivity (327 positive/810 total sera tested; 40.37%) was attained when the positive results to the six viruses were added together. No association could be found between any particular type or subtype of virus and the sensitivity of the test. When positive results to each single strain were considered, SN sensitivity varied from 41.7% to 81.7%, depending on the virus and the geographic region of origin of the sera. Variation was detected even when challenge viruses belonged to the same subtype, where disagreement between positive results reached 41%. These results indicate that one hour incubation SN tests against single viruses, as performed here, may display a significantly low sensitivity (p=0.05); performing SN tests against a number of different viruses may increase considerably SN sensitivity. Furthermore, the choice of virus used for challenge is critical in SN tests. In addition, sera from different geographic regions may give rise to disagreeing results with different strains of BoHV-1 and BoHV-5. This might be particularly relevant for control programs and in international trade, were maximum sensitivity should be targeted.